Taḥlīl aṣ-Su‘ūbāt Allatī Yuwāji-hā ṭullāb aṣ-Saff ar-Rābi‘ al-Ibtidā’ī fīī at-Ta‘rīf bīī-Anfusihim bi-Isti‘māl al-Lughah al-‘Arabiyyah fīī Madrasah al-Ibtidā’iyyah Bina Insan Batang Kuīs - Lestari, Dwi; Nasution, Adil Fathi (Al Maghazi : Arabic Language in Higher Education, 2024)
Students' difficulties in learning Arabic, especially in reading and writing skills due to limited vocabulary mastery, are the background to this study. This study aims to analyze the difficulties faced by 4th grade students of Bina Insan Batang Kuis Elementary School in introducing themselves using Arabic. The method used in this research is using qualitative approach with descriptive design. This study took research subjects from 30 students and one Arabic language teacher in grade 4 of Bina Insan Batang Kuis Elementary School. The research data were collected through in-depth interviews with the Arabic language teacher, direct observation in teaching and learning activities, and questionnaires distributed to students to identify the types of difficulties experienced by students in grade 4 of Bina Insan Batang Kuis Elementary School. The results of the analysis show that students experience difficulties in mastering Arabic vocabulary, Arabic sentence structure, and low self-confidence when speaking Arabic. These difficulties are caused by the influence of the mother tongue and the daily or local language used by the students which has a much different language structure, sentence structure and vocabulary and letters used. This study also emphasizes the importance of more interactive teaching methods and additional support in Arabic language learning to improve students' ability to use Arabic. The findings of this study are expected to serve as a basis for teachers and curriculum developers in designing more effective learning strategies.